Volunteering and instrumental support during the first phase of the pandemic in Europe: the significance of COVID-19 exposure and stringent country's COVID-19 policy - Septi Kurnia Lestari; Malin Eriksson; Xavier de Luna; Gunnar Malmberg; Nawi Ng (BMC, 2024)
Abstract Background The COVID-19 control policies might negatively impact older adults' participation in volunteer work, instrumental support provision, and the likelihood of receiving instrumental support. Studies that quantify changes in these activities and the related factors are limited. The current study aimed to examine the level of volunteering, instrumental support provision and receipt before and during the first phase of the COVID-19 pandemic in Europe and to determine whether older adults' volunteering, instrumental support provision and receipt were associated with individual exposure to COVID-19 and the stringency of country's COVID-19 control policy during the first phase of the COVID-19 pandemic. Methods A cross-sectional survey using data from the Survey of Health, Ageing and Retirement in Europe (SHARE) Corona Survey 1 was designed to focus on community-dwelling Europeans aged ≥50 years. History of participation in volunteering work and instrumental support provision or receipt was assessed from the previous SHARE Wave data. The country's COVID-19 control policy stringency index (S-Index) was from the Oxford COVID-19 Government Response Tracker database. A total of 45,669 respondents from 26 European countries were included in the volunteering analysis. Seventeen European countries were included in the analyses of instrumental support provision (N = 36,518) and receipt (N = 36,526). The multilevel logistic regression model was fitted separately to analyse each activity. Results The level of volunteering and instrumental support provision was lower during the pandemic, but instrumental support receipt was higher. The country S-Index was positively associated with support provision (OR:1.13;95%CI:1.02-1.26) and negatively associated with support receipt (OR:0.69;95%CI:0.54-0.88). Exposure to COVID-19 was positively associated with support receipt (OR:1.64;95%CI:1.38-1.95). COVID-19 exposure on close ones positively associated with volunteering (OR:1.47;95%CI:1.32-1.65), support provision (OR:1.28;95%CI:1.19-1.39), and support receipt (OR:1.25;95%CI:1.15-1.35). Conclusions The COVID-19 pandemic impacted older Europeans' volunteering, instrumental support provision, and instrumental support receipt from outside their household. When someone close to them was exposed to COVID-19, older Europeans were likely to receive instrumental support and to volunteer and provide instrumental support. A stricter country's COVID-19 control policy might motivate older adults to provide instrumental support, but it prevents them from receiving instrumental support from outside their households.